PENINGKATAN PENGETAHUAN TENTANG PENTINGNYA KESELAMATAN DAN KESEHATAN KERJA (K3) PADA TENAGA KERJA HOUSE KEEPING TERHADAP KINERJA ROOMBOY DI HOTEL - Novrizal Ramadan (Jurnal Kesehatan, 2023)
This journal is entitled "Increasing Knowledge About the Importance of Occupational Safety and Health (K3) in House Keeping Workers on Roomboy Performance in Hotels". The goal to be achieved from writing this journal is to find out the efforts to improve Roomboy performance in housekeeping operations, To find out things that must be done in increasing Knowledge About the Importance of Occupational Safety and Health (K3) in House Keeping Workers on Roomboy Performance in Hotels. Based on the discussion in this journal, the author will discuss the concept of Occupational Health and Safety. The problem that the author proposes is how to increase knowledge about the importance of occupational safety and health (K3) in house keeping workers on roomboy performance in hotels so that roomboy performance can be maximized.